Pendidikan Islam Dalam Perspektif Hasan Langgulung - Khafizoh, Syahrul Kodrah, Zaifatur Ridha (Khazanah : Journal of Islamic Studies, 2023)
This research is based on the phenomenon that Islamic education has now lost its essence and identity towards the purpose of human life because the concept used does not yet reflect Islamic values ??for the moral declaration of the nation's children. This shows that Islamic education needs to be reformed. So that this research raises the idea of ??Hasan Langgulung who is an expert and scientist who no doubt has his abilities in the fields of education and psychology. This is proven by the many works he has produced. From these ideas that will be studied are: (1) regarding educational goals, the function of philosophy in education, educational values, and educational curriculum; (2) explaining the ideal role of educators according to Hasan Langgulung. This research is a library research (library research). The approach used in this study is a philosophical approach. This research is a qualitative research, so the method used to analyze the data is content analysis method. The results of this study are: (1) The purpose of Islamic education and the role of educators according to Hasan Langgulung is a goal that focuses on trust and worship, this is intended to be in accordance with the goals of human life. Philosophy in education is needed so that there is no dichotomy of curriculum content, which is a design activity for the educational process in achieving the goals studied from God's verses both in the Qur'an and Hadith in text and in the universe and humans in their creators. Then regarding the discussion of values ??in Islamic education is something that must be inherited in the world of Islamic education. without values, the integrity and unity of a society will not be maintained which will eventually end in the destruction of that society. As for the sources of value that should be seen for Islamic education in maintaining the values ??of the younger generation, namely: Al-Qur'an and Sunnah.